Isolation and Identification of Rickettsia raoultii in Human Cases: A Surveillance Study in 3 Medical Centers in China. (23rd October 2017) - Li, Hao; Zhang, Pan-He; Huang, Yong; Du, Juan; Cui, Ning; Yang, Zhen-Dong; Tang, Fang; Fu, Fei-Xiang; Li, Xiao-Mei; Cui, Xiao-Ming; Fan, Ya-Di; Xing, Bo; et al.
Abstract : We identified that Rickettsia raoultii infection could cause a wide clinical spectrum of illness ranging from subclinical infection to severe complications. Rickettsia raoultii strain IM16 has more intact genes than several more virulent Rickettsia species, indicating a low pathogenicity of the strain. Abstract: Background: Rickettsia raoultii is frequently detected in multiple tick species, whereas human infection remains scarcely studied. Methods: A surveillance study was performed at 3 sentinel hospitals in China, to recruit participants with suspected tick exposure. Rickettsia raoultii infection was identified through polymerase chain reaction, followed by sequencing, and confirmed serologically. Isolation by cell culture was performed and the isolates were genome sequenced. Results: Twenty-six subjects were determined to have R. raoultii infection, including 7 with asymptomatic infection, 15 with mild to moderate illness, and 4 with severe illness. Common nonspecific manifestations in the 19 patients with mild to moderate or severe illness included fever (100%), malaise (95%), myalgia (58%), lymphadenopathy (53%), and nausea (42%). Only 5% of them had rash, and 16% had eschar. Scalp eschar and neck lymphadenopathy after a tick bite syndrome was only seen in 2 patients. Of the 4 patients with severe complications, 3 developed pulmonary edema, and 1 developed clouding of consciousness and lethargy. Frequent abnormalities of laboratory testing included leukopenia, thrombocytopenia, lymphopenia, neutropenia, hypoproteinemia, and elevated levels of total bilirubin, hepatic aminotransferases, lactate dehydrogenase, and creatine kinase. All the 19 patients recovered without sequelae after receiving doxycycline treatment. Two R. raoultii strains were isolated, and a significantly less degraded genome was observed than other more virulent Rickettsia strains, indicating a low pathogenicity of the current strain. Conclusions: Human infection with R. raoultii has a wide clinical spectrum that ranged from subclinical infection to severe complications. Physicians need to be aware of the high potential and clinical complexity of R. raoultii infection, to ensure appropriate testing and treatment in endemic regions.